Preburnt and postburnt fynbos standing crop at Pella, Cape - O'Callaghan, Mike (Department of Biological Sciences, 2021)
At Pella research station , 20 year-old fynbos standing crop was determined by cropping eight 2m x 2m plots and felling five Protea repens trees in an unburnt area . A regression was also performed between the dry mass of the P. reopens trees (kg) and their stem diameter (cm). It was estimated that the total preburnt P. repens plant material was 24 125,34 kg/ha dry mass and the total plant material for the other shrubs was 15 149 kg/ha dry mass. The 20 year-old postburnt standing crop was determined by cropping three 2m x 2m plots and felling three P. repens in a burnt area. It was found that the postburnt P. repens material was 9 409 kg/ha dry mass and the other shrubs was 2 kg/ha dry mass . The total preburnt plant material was 3S 274,34 kg/ha dry mass and the total postburnt plant material was 9 411,76 kg/ha dry mass. Thus , 29 862,58 kg/ha dry mass was consumed by the fire, an equivalent of 76,04 %.